Effects of Coefficient of Thermal Expansion and Moisture Absorption on the Dimensional Accuracy of Carbon-Reinforced 3D Printed Parts - Jessica L. Faust (MDPI AG, 2021)
Environmental effects—temperature and moisture—on 3D printed part dimensional accuracy are explored. The coefficient of thermal expansion of four different nylon materials was determined for XY and ZX print orientations, with 0°, 45°/−45°, and 90° infill patterns. Unreinforced nylon exhibited a thermal expansion coefficient of the same order regardless of condition (from 11.4 to 17.5 × 10−5 1/°C), while nylons reinforced with discontinuous carbon fiber were highly anisotropic, for instance exhibiting 2.2 × 10−5 1/°C in the flow direction (0° infill angle) and 24.8 × 10−5 1/°C in the ZX orientation. The temperature profile of a part during printing is shown, demonstrating a build steady state temperature of ~ 35 °C. The effect of moisture uptake by the part was also explored, with dimensional changes of ~0.5–1.5% seen depending on feature, with height expanding the most. The effects of moisture were significantly reduced for large flat parts with the inclusion of continuous fiber reinforcement throughout the part.